Pests and diseases of trees in Africa: A growing continental emergency. Issue 1 (2nd June 2019) - Graziosi, Ignazio; Tembo, Mathias; Kuate, Jean; Muchugi, Alice
Abstract : Societal Impact Statement: The increasing occurrence of native and non‐native pests and diseases of trees in Africa is impacting rural livelihoods, economic development, and biodiversity across the continent. Here we provide an updated and comprehensive overview of insect pests and pathogens targeting natural and planted forests in Africa, and raise awareness of this growing emergency. Data availability and limited biosecurity of some countries are limiting the ability to tackle this invasion. An improved knowledge of taxonomy, distribution, and damage caused by these organisms will be crucial for developing continent‐wide strategies to manage this emergency and enhance country‐level intervention capacity. Summary: An increasing multitude of insect pests and pathogens is targeting indigenous trees of natural forests, agroforestry systems, and exotic trees in planted forests in Africa. This is raising major concerns for a continent already challenged by adaptations to climate change, as it threatens a vital resource for food security of rural communities, economic growth, and ecosystem conservation. The accidental introduction through trade of non‐native species in particular is accelerating, and it adds to the damage to tree‐based landscapes by native pests and diseases. Old‐time and new invaders heavily impact planted forests of exotic eucalypts, pines, and acacias, and are spreading quickly across African regions. But many non‐native pathogens are recently found affecting important indigenous trees. We describe the threat to African trees by providing an overview of highly relevant insect pests and diseases of indigenous and exotic trees in Africa, and discuss implications for management and future research. The implementation of an integrated and globally coordinated approach based on improved biosecurity, biological control, and tree resistance would contribute to mitigate the potentially devastating impact of these invasions on African natural resources. Abstract : The increasing occurrence of native and non‐native pests and diseases of trees in Africa is impacting rural livelihoods, economic development, and biodiversity across the continent. Here we provide an updated and comprehensive overview of insect pests and pathogens targeting natural and planted forests in Africa, and raise awareness of this growing emergency. Data availability and limited biosecurity of some countries are limiting the ability to tackle this invasion. An improved knowledge of taxonomy, distribution, and damage caused by these organisms will be crucial for developing continent‐wide strategies to manage this emergency and enhance country‐level intervention capacity.